A bibliometric review of research on COVID-19 and tourism: Reflections for moving forward. (October 2021) - Utkarsh,; Sigala, Marianna
Abstract: By adopting a bibliometric analysis approach, this study systematically reviews and retrospectively analyses the rapidly emerging literature on COVID-19 in tourism and hospitality. A co-word analysis revealed the intellectual structure of 177 papers (published until January 2021) consisting of four major themes discussing the following various issues: 1) the impact of COVID-19 on tourist decision-making, destination marketing, technology adoption, and tourists' well-being; 2) the future of tourism post COVID-19; 3) managing change in tourism; and 4) the COVID-19's impacts on tourism and hospitality stakeholders. The findings show that preliminary publications tend to be descriptive, pre-mature and theoretical, i.e. most studies advocate and re-imagine a more sustainable, responsible and equitable post-pandemic tourism, but almost no research investigates in-depth whether, why and how such theoretical proclamations are being materialized or not and/or whether they will remain a COVID-19 induced fuss. The paper concludes by offering various directions and propositions for future research. Highlights: A bibliometric review of 177 articles about COVID-19 within tourism and hospitality Bibliometric metrics revealed the knowledge structure consisting of four major themes Future research directions and propositions are suggested to address the identified research gaps